Impaired B Cell Apoptosis Results in Autoimmunity That Is Alleviated by Ablation of Btk - Wright, Jacqueline A.; Bazile, Cassandra; Clark, Emily S.; Carlesso, Gianluca; Boucher, Justin; Kleiman, Eden; Mahmoud, Tamer; Cheng, Lily I.; López-Rodríguez, Darlah M.; Satterthwaite, Anne B.; Altman, Norman H.; Greidinger, Eric L.; et al. (Frontiers in Immunology, 2021)
While apoptosis plays a role in B-cell self-tolerance, its significance in preventing autoimmunity remains unclear. Here, we report that dysregulated B cell apoptosis leads to delayed onset autoimmune phenotype in mice. Our longitudinal studies revealed that mice with B cell-specific deletion of pro-apoptotic Bim (BBimfl/fl) have an expanded B cell compartment with a notable increase in transitional, antibody secreting and recently described double negative (DN) B cells. They develop greater hypergammaglobulinemia than mice lacking Bim in all cells and accumulate several autoantibodies characteristic of Systemic Lupus Erythematosis (SLE) and related Sjögren’s Syndrome (SS) including anti-nuclear (ANAs), anti-Ro/SSA and anti-La/SSB at a level comparable to NODH2h4 autoimmune mouse model. Furthermore, lymphocytes infiltrated the tissues including salivary submandibular glands (SG) and formed germinal center-like structures populated with B cells, plasma cells and T follicular helper cells indicative of ongoing immune reaction. This autoimmunity was ameliorated upon deletion of Bruton’s tyrosine kinase (Btk) gene, which encodes a key B cell signaling protein. These studies suggest that Bim-mediated apoptosis suppresses and B cell tyrosine kinase signaling promotes B cell-mediated autoimmunity.